The Development of Science Learning Media Using Android Applications in Solar System Subject - Riris Apriliana; Murfiah Dewi Wulandari (Universitas Pahlawan Tuanku Tambusai, 2022)
This research uses the R&D (Research and Development). The model used in this research is ADDIE (Analysis, Design, Development, Implementation, and Evaluation), but researcher only limit it to the development stage. This study aims to produce and test the feasibility of Android-based science learning media in solar system subjects, especially in the sixth-grade. Data collection techniques used are literature studies and questionnaires/questionnaires. The product feasibility test is carried out by media experts and material experts. The data analysis technique was carried out qualitatively and quantitatively. Based on the feasibility test conducted by the experts, it can be seen that the validation results by media experts obtained an average of 4.69 so it indicated the